Estudio De Tiempos Y Rendimientos En La Transformacion De Trozas De Madera Pinus Radiata D. Don (Pino) En Tablas Para La Elaboracion De Pallets - Eduardo Cevallos; Ximena Lara; Janneth Morocho; Martha Dávalos; Eduardo Salazar; Sulema Lara (European Scientific Journal, ESJ, 2017)
This present study gives an estimation of the time and efficiency in the transformation of pine logs into boards for the manufacturing of pallets in the industry, Haro Madera. Here, the percentage of the wood used and the percentage of sawdust were determined. This was with a yield of 34.936% in the processing of the logs, 43.29% into square posts, and 15.08% in the direct transformation of the logs into boards. In order to determine the factors that affect the production of pine lumber, the wood was classified by its length, diameter, and shape where it was possible to determine its influence in the production into boards. This, therefore, proves that the qualitative factors are influential in the elaboration of the boards to construct pallets, in terms of time. Also, it was possible to determine that for the manufacture of an American type pallet, it took 10.24 minutes, while the European type pallet took 13.9 minutes. To determine the output per machine, a sampling was used. Here, specific observations were made, dividing working time and non-working time. Wood utilization percentage was low, the production line must be improved, and the logs from different plantations should be classified according to their diameter and shape.